(untitled) (JED (Jurnal Etika Demokrasi), 2025)
This study addresses the pressing need to improve student engagement and learning outcomes in civic education through innovative pedagogical strategies. The research aimed to evaluate the effectiveness of integrating quantum teaching with crossword puzzle media in enhancing conceptual mastery and values-based learning among junior secondary school students. Employing a quantitative experimental design, the study involved a one-group pretest-posttest approach with 37 seventh-grade students, utilizing standardized tests and validated questionnaires to assess both cognitive achievement and affective responses. Statistical analysis revealed a significant increase in students’ post-intervention scores, with all participants reaching mastery and demonstrating greater enthusiasm, motivation, and participation. The findings highlight that the application of the TANDUR framework, reinforced by interactive media, creates a dynamic and inclusive learning environment that bridges the gap between knowledge acquisition and civic value internalization. The study concludes that quantum teaching with crossword puzzles substantially elevates both academic achievement and affective engagement in civic education. The novelty of this research lies in its empirical validation of a synergistic approach, combining holistic pedagogy with game-based media, which had not been systematically examined in previous studies. This work contributes to the advancement of educational practice by providing robust evidence for the adoption of active, student-centered, and values-oriented instructional models in contemporary classrooms.